(untitled) (Journal of the College of Basic Education, 2024)
The purpose of this study is to explore the online complaints techniques utilized by Facebook users directed to the Iraqi Ministry of Electricity IMOE platform. This study also attempts to determine the most common techniques employed by Facebook users, as well as to identify the verbal and nonverbal languages utilized by IMOE users about the IMOE page. This study aims to fill the knowledge gap about the expression of online complaints by Iraqi speakers, as far as the researcher is aware, no research has been conducted in this area. The analytical framework of Olshtain and Weinbach (1987), and Trosborg (1994)) were used to analyze the data. In addition, the researcher found six new techniques, which were included in the adopted strategies. The study has ended with some results based on the practical analysis and frequency found in the corpus.